A Association of Knowledge, Behavior, and Environmental Sanitation with Helminthiasis among Children Aged 7–9 Years in Namo Sialang Village, 2024: Association of Knowledge, Behavior, and Environmental Sanitation with Helminthiasis among Children Aged 7–9 Years in Namo Sialang Village, 2024 - Nova Apriliana Nainggolan (Jurnal Kedokteran Methodist, 2025)
Background: Intestinal worms are diseases caused by infections from worms that reside in the soil. Children's understanding of personal hygiene is crucial, as good knowledge about intestinal worms can promote preventive actions. The high prevalence of worm infections is influenced by factors affecting the life cycle of these worms, such as poor environmental sanitation, inadequate personal hygiene, and the socioeconomic conditions of the community. Objective: This study aims to identify the relationship between knowledge of intestinal worms, behavior, and environmental hygiene among children aged 7-9 years in Namo Sialang Village in 2024. Method: This research is a correlational study with a cross-sectional design. Result: The study involving 49 samples revealed a significant relationship between knowledge and the prevalence of worm infections (p = 0.003), as well as between behavior and worm infection occurrence (p = 0.002). Environmental sanitation also showed a significant correlation with worm infections (p = 0.010). Conclusion: This conclusion indicates a significant relationship between knowledge, behavior, and environmental sanitation with the occurrence of intestinal worms. In terms of distribution, the level of knowledge influences the prevalence of worm infections.